Spiritual Continuum of Bessarabian Artist Ivan Shishman Creativity - Tetyana Shevchuk (Journal of Danubian Studies and Research, 2018)
The article deals with the spiritual space of creativity of the modern Bessarabian artist Ivan Shishman, who is a member of the National Union of Artists of Ukraine and Honored Artist of Ukraine. I. Shishman’s achievements are represented by the series of creative compositions, restoration works, sacred paintings and its conservation, as well as icon painting.